Treatment strategies in mucous membrane pemphigoid - Ann G Neff; Matthew Turner; Diya F Mutasim (Dove Medical Press, 2008)
Ann G Neff, Matthew Turner, Diya F MutasimDepartment of Dermatology, University of Cincinnati, Cincinnati, OH, USAAbstract: Mucous membrane pemphigoid (MMP) is an autoimmune blistering disorder that is characterized by subepithelial bullae. Various basement membrane zone components have been identified as targets of autoantibodies in MMP. Considerable variability exists in the clinical presentation of MMP. Mucous membranes that may be involved include the oral cavity, conjunctiva, nasopharynx, larynx, esophagus, genitourinary tract, and anus. A multidisciplinary approach is essential in the management of MMP. Early recognition of this disorder and treatment may decrease disease-related complications. The choice of agents for treatment of MMP is based upon the sites of involvement, clinical severity, and disease progression. For more severe disease, or with rapid progression, systemic corticosteroids are the agents of choice for initial treatment, combined with steroid-sparing agents for long-term maintenance. Due to the rarity of this disease, large controlled studies comparing the efficacy of various agents are lacking.Keywords: mucous membrane pemphigoid, cicatricial pemphigoid